A modified Sequential Organ Failure Assessment score for dengue: development, evaluation and proposal for use in clinical trials - McBride, A; Vuong, NL; Van Hao, N; Huy, NQ; Chanh, HQ; Chau, NTX; Nguyet, NM; Ming, DK; Ngoc, NT; Nhat, PTH; Phong, NT; Tai, LTH; et al. (BioMed Central, 2022)
Background: Dengue is a neglected tropical disease, for which no therapeutic agents have shown clinical efficacy to date. Clinical trials have used strikingly variable clinical endpoints, which hampers reproducibility and comparability of findings. We investigated a delta modified Sequential Organ Failure Assessment (delta mSOFA) score as a uniform composite clinical endpoint for use in clinical trials investigating therapeutics for moderate and severe dengue.